Regulacje prawne dotyczące władzy rodzicielskiej jako wyraz kultury prawnej. Ujęcie pedagogiczne - Kopińska, Violetta (Wydawnictwo Naukowe UAM, 2014)
In this paper I analyze Polish legal regulations connecting with the implementation of parental authority from the perspective of legal culture. Contemporary law stresses the importance of the child’s well-being, the need to respect his rights and dignity. Legal provisions do not lead to a high density in this sphere of social relations, but allow some degree of interventionism in particularly serious situations and clearly emphasize the principle of subsidiarity. The pedagogical perspective, however, allows to highlight several problems. In this paper I refer to the recently introduced prohibition of corporal punishment of children. Furthermore, I analyze the concept of parental authority and respond to the concept of the child’s well-being, which - in my opinion - is a threat to the functionality of legal culture, especially in the field of creation and application of law.
Legal Regulations Concerning Parental Authority as an Expression of Legal Culture. A Pedagogical Perspective
Keywords: family; parental authority; subsidiarity; legal culture